No causal effect of genetically determined circulating homocysteine levels on psoriasis in the European population: evidence from a Mendelian randomization study - Chen, Chaojian; Liu, Shuo; Liu, Junhao; Zheng, Ziqi; Zheng, Yixi; Lin, Zhongliang; Liu, Yuchun (Frontiers in Immunology, 2023)
Background: Although numerous studies demonstrated a link between plasma homocysteine (Hcy) levels and psoriasis, there still exists a certain level of controversy. Therefore, we conducted a mendelian randomization study to investigate whether homocysteine plays a causative role in the development or exacerbation of psoriasis. Methods: A two-sample Mendelian randomization (MR) analysis was conducted. Summary-level data for psoriasis were acquired from the latest R9 release results from FinnGen consortium (9267 cases and 364,071 controls). Single-nucleotide polymorphisms (SNPs) robustly linked with plasma Hcy levels at the genome-wide significance threshold (p < 5×10 -8 ) (18 SNPs) were recognized from the genome-wide meta-analysis on total Hcy concentrations (n = 44147 participants) in individuals of European ancestry. MR analyses were performed utilizing the random-effect inverse varianceweighted (IVW), weighted median and MR-Egger regression methods to estimate the associations between the ultimately filtrated SNPs and psoriasis. Sensitivity analyses were conducted to evaluate the heterogeneity and pleiotropy. Results: MR analyses revealed no causal effects of plasma Hcy levels on psoriasis (IVW: odds ratio (OR) = 0.995 (0.863-1.146), p = 0.941; weighed median method (OR = 0.985 (0.834-1.164), p= 0.862; MR-Egger regression method (OR = 0.959 (0.704-1.305), p = 0.795). Sensitivity analyses displayed no evidence of heterogeneity and directional pleiotropy and that the causal estimates of Hcy levels were not influenced by any individual SNP. Conclusion: Our study findings did not demonstrate a causal effect of genetically determined circulating Hcy levels on psoriasis.